Investor behavior in gold, US dollars and cryptocurrency during global pandemics - Yoochan Kim; Erkan Topal; Apurna Kumar Ghosh; Mohammad Waqar Ali Asad (Economies, 2023)
COVID-19 and SARS are epidemics which have influenced the largest global economic crisis in recent years. This research reveals that both SARS and COVID-19 have led to fluctuations in the prices of gold and the US dollar index; however, there is no direct causal relationship be-tween COVID-19 and the price of bitcoin. The USD index saw a significant increase during the SARS outbreak, while gold prices surged during the COVID-19 pandemic. The notion that cryptocurrency will surpass the value of gold or traditional currencies seems improbable, given the lack of evidence linking bitcoin prices to COVID-19. Gold is expected to maintain its value in the long term, offering lower risk compared to other currencies.
Keywords: 330; gold price; COVID-19; US dollars; bitcoin price; Granger causality; Johansen co-integration; vector error correction model